Gangte Pauzilna Leh Paugawpdan – Pawl IX and X | Gangte Grammar and Composition – Class IX and X - (:unkn) unknown (The Gangte Literature Society, Manipur, 2015)
This is a school textbook on Grammar and composition for class IX and X written in Gangte.
Keywords: Gangte; Grammar & Composition; Gangte